FUNDAMENTAL HUMAN RESOURCE MANAGEMENT CONCEPTS FOR ISLAMIC EDUCATIONAL INSTITUTIONS: FOSTERING CHARACTER AND RELIGIOUS VALUES THROUGH STRATEGIC WORKFORCE DEVELOPMENT - Basit, Abdul; Ahmad, Aprizal; Azhari, Devi Syukri; Ingriza, Resva; Qurba, Alqanit (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
In Islamic educational institutions, Human Resource Management (HRM) plays a critical role not only in supporting organizational sustainability but also in nurturing a workforce that aligns with Islamic values. HRM in this context goes beyond traditional personnel management, aiming to recruit, develop, and evaluate educators and staff who exemplify Islamic morals and ethics. By strategically planning, managing, and supervising human resources, Islamic institutions can create an environment that fosters moral integrity, religious attitudes, and a commitment to lifelong learning. This article explores foundational HRM concepts, with a focus on their application in Islamic education to enhance character formation, strengthen religious values, and support academic excellence